Aggregatibacter actinomycetemcomitans in African Americans with Localized Aggressive Periodontitis. (July 2017) - Burgess, D.; Huang, H.; Harrison, P.; Aukhil, I.; Shaddox, L.
This study aims to investigate the prevalence of the highly leukotoxic JP2 sequence versus the minimally leukotoxic non-JP2 sequence of Aggregatibacter actinomycetemcomitans within a cohort of 180 young African Americans, with and without localized aggressive periodontitis (LAP), in north Florida. The study included patients aged 5 to 25 y: 60 LAP patients, 60 healthy siblings (HS), and 60 unrelated healthy controls (HC). Subgingival plaque was collected from LAP sites—diseased (PD ≥5 mm with bleeding on probing) and healthy (PD ≤3 mm with no bleeding on probing)—and from healthy sites of HS and HC. Plaque DNA was extracted and analyzed by polymerase chain reaction for the detection of the JP2 and non-JP2 sequences of A. actinomycetemcomitans . Overall, 90 (50%) subjects tested positive for the JP2 sequence. Fifty (83.33%) LAP subjects were carriers of the highly leukotoxic JP2 sequence, detected in 45 (75%) diseased sites and 34 (56.67%) healthy sites. Additionally, JP2 carriage was found in 16 HS (26.67%) and 24 HC (40%; P < 0.0001, among groups). The non-JP2 sequence was detected in 26 (14.44%) total subjects: 17 (28.33%) LAP patients detected in equal amounts of diseased and healthy sites ( n = 11, 18.33%), 6 (10%) HS sites, and 3 (5%) HC sites ( P < 0.05, among groups). The JP2 sequence was strongly associated with LAP-diseased sites in young African Americans, significantly more so than the non-JP2 (ClinicalTrials.gov NCT01330719). Knowledge Transfer Statement : Clinicians may use the results of this study to identify susceptible individuals to aggressive periodontitis, potentially leading to more appropriate selection of therapeutic choices.